Opportunities and Challenges: E-Commerce in Indonesia from a Legal Perspective - Edy Santoso (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
The development of e-commerce in Indonesia has encouraged the creation of a digital economy. On the other hand, this business model presents various legal challenges that are no less interesting to anticipate. By applying normative research methods and using statutory and comparative law approaches, this study examines two issues. First, what are the legal aspects that are used as the basis for the role of Information and Communications Technology (ICT) in capturing e-commerce opportunities? Second, what are the legal challenges ahead with the rapid growth of e-commerce in Indonesia? This study concludes that normatively Indonesia already has various regulations in the field of cyber law that support the use of ICT in e-commerce. However, it needs specific regulation. This study finds things that will become legal challenges in the future, including there are still gaps for parties to commit violations and crimes, especially in the fields of data theft, intellectual property, fraud, and breach of contract. This study provides the suggestion that the government should pay attention to security-related regulations, especially those related to personal data security. It requires the role of business actors in making